2017
DOI: 10.24198/pjd.vol29no1.11654
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potency of black sea cucumber (Holothuria atra) from Mentawai Islands, Indonesia

Abstract: Introduction:The source of bioactive compounds believed to have strong anticancer potency is derived from sea cucumber. Black sea cucumber (Holothuria atra) is a dominant species in Mentawai Islands, West Sumatera, Indonesia. Key factor compound that acts as anticancer in sea cucumber extract is tritepenoid also known as Frondoside A. The purpose of this study was to determine the effectiveness of the active compound taken from black sea cucumber as anticancer. Methods: Methods used was experimental laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Black sea pepper seems to exaggerate chronic cough [16] instead of alleviating it, although Largus does not state which species of pepper he would use. The potential anticancer effect of black sea peper may justify its use against lymphadenopathy, however, this must have been masking the symptoms of neoplastic diseases rather than helping manage them [17].…”
Section: Nutraceuticals In Ancient Rome: Clinical Practice and Implic...mentioning
confidence: 99%
“…Black sea pepper seems to exaggerate chronic cough [16] instead of alleviating it, although Largus does not state which species of pepper he would use. The potential anticancer effect of black sea peper may justify its use against lymphadenopathy, however, this must have been masking the symptoms of neoplastic diseases rather than helping manage them [17].…”
Section: Nutraceuticals In Ancient Rome: Clinical Practice and Implic...mentioning
confidence: 99%
“…This sea cucumber had the highest cytotoxicity among 15 species of sea cucumbers collected from Gorontalo, Indonesia [8]. In addition, ethanolic extract of H. atra has potential cytotoxicity against several cancer cell lines, namely T47D, HeLa, WiDr [9], HepG2 [10], SP-C1 [11], A549, and B16F10 [12]. Ethanol extract of H. atra could induce apoptosis and activate caspase-3 in T47D cells [13].…”
Section: Introductionmentioning
confidence: 97%
“…So far, around 150 types of saponins have been identified from sea cucumbers of class Holothuroidea (Honey-Escandón et al, 2015). Results of previous studies reported that the sea cucumber Holothuria atra had promising cytotoxicity against several cancer cell lines, namely human breast ductal carcinoma (T47D), human cervix epitheloid carcinoma (HeLa), human colon adenocarcinoma (WiDr), human Caucasian hepatocyte carcinoma (HepG2), and human oral tongue squamous cell carcinoma (SP-C1) (Satari et al, 2017;Halimatushadyah et al, 2018). Furthermore, the ethanolic extract of H. atra showed induction of apoptosis and caspase-3 activation in T47D breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%